Thermal Conductivity of Foamed Concrete Fibre Arenga Pinnata Merr - Yunita .; Nasrullah Idris; Abdullah . (PSI-Aceh, 2012)
The objective of this research is to examine the effect of the palm fibre from arenga pinnata Merr on thermal conductivity of foamed concrete. The sample was made at civil Engineers Departement labolatory with specific gravity of 1.0 and 1.4 with variations of the palm fibre from arenga pinnata Merr are 0.5 %, 1.0 %, and 2.0 %. The sample was packed into (15 x 15 x 1) cm3. The measurement result showed that the thermal conductivity values are increase with the small porosity, i.e. 18 %, on the contrary, the thermal conductivity values are decrease with the large porosity, i.e. 27 %. The thermal conductivity values of concrete the palm fibre from arenga pinnata Merr addiction are 0.47 W/mºC, 0.52, W/mºC, and 0.44 W/mºC for specific gravity values 1.0 with 0.5 %, 2.0 %, and 2 %. It about 0.48 W/mºC, 0.45 W/mºC and 0.43 W/mºC for specific gravity values 1.4 with 0.5 %, 1.5 %, and 2.0 %. In conclusion, the thermal conductivity values of foamed concrete with the palm fibre arenga pinnata Merr addiction has the largest value in specifict gravity 1.0 with 2.0 % of the palm fibre arenga pinnata Merr percentage